Systematic review on rapidity of onset of action for interleukin‐17 and interleukin‐23 inhibitors for psoriasis. (10th October 2019) - Egeberg, A.; Andersen, Y.M.F.; Halling‐Overgaard, A.‐S.; Alignahi, F.; Thyssen, J.P.; Burge, R.; Mallbris, L.
Abstract: Several novel biologics are available or in development for moderate‐to‐severe plaque psoriasis. These drugs may differ in time until Psoriasis Area and Severity Index (PASI) response is obtained. In this systematic review, we examined the time to onset of action for interleukin (IL)‐17 and IL‐23 agents in the treatment of psoriasis. The primary objective was the weighted mean time needed for 25% and 50% of patients with psoriasis to achieve PASI90. The medical databases PubMed, Web of Science and EMBASE were searched using the following terms: psoriasis AND (ixekizumab OR secukinumab OR brodalumab OR risankizumab OR guselkumab OR tildrakizumab). A total of 27 studies were included for data extraction and qualitative synthesis, and 26 of these were quantitatively analysed. The shortest time to 25% and 50% of patients to achieved PASI90 were seen with brodalumab 210 mg every 2 weeks (Q2W; 3.5 weeks and 6.2 weeks, respectively) followed by ixekizumab 80 mg Q2W (4.1 and 7.4 weeks, respectively) and ixekizumab 80 mg Q4W (4.6 and 8.1 weeks, respectively) dosages. In conclusion, clinical trials yielded shorter time to onset of action in studies assessing approved dosing ranges of IL‐17 inhibitors compared with studies assessing IL‐23 inhibitors.